How is employees' input and influence over collective agreements shaped by Australia's Fair Work Act?. (2nd July 2016) - Walpole, Kurt
ABSTRACT: Employees appear as relatively passive figures in most analyses of the Fair Work Act's collective agreement-making process because official bargaining representatives negotiating in formal meetings have been the focus of attention. This article re-examines how the Act structures employee participation in the agreement-making process, with a particular focus on the degree or depth of employee input and influence over the agreement's terms. Drawing on Flanders' 'political view of collective bargaining', the formalistic legal analysis indicates that the Act facilitates different kinds of employee input and influence at different stages of the agreement-making process. The article concludes that employee input through a yes/no vote to be bound by an employer's proposed agreement is prioritised the Act. While the legitimacy of an agreement is premised on this level of employee input, the Act allows employee influence over the terms and content of an agreement to vary considerably between cases.